The nuclearity of sonorous consonants after vowels and diphthongs resulting from the elision of the schwa sound in standard German - Skoczek, Robert (Papers in Linguistics, 2025)
The shwa sound [ə] in the ending <-en> is considered an indicator of the phonostylistic differentiation of standard German. The nuclearity of sonorous consonants after vowels and diphthongs is handled differently in the literature of the subject and in pronunciation codes. The article assumes the phonological and phonetic perspective and attempts to determine whether sonorous consonants in such a distribution are syllabic.